Outcome at Six Months After Primary Percutaneous Coronary Interventions Performed at a Rural Satellite Center of Sindh Province of Pakistan - Mujtaba, Syed F (Cureus, 2020)
Introduction Primary percutaneous coronary intervention (PPCI) is now a well-established treatment of acute ST-elevation myocardial infarction (STEMI). For the first time in Pakistan, various off-site satellite centers are established to perform PPCI 24-hours. Our population mainly resides in the rural area with low literacy rate and poor socioeconomic conditions. The majority of the patients who are presented in the satellite center had either never received any long-term treatment plan or were non-compliant to their medication. The objective of this study was to determine the outcome of patients at six months who underwent primary PCI at a rural satellite center of Sindh, Pakistan. Methods This study was conducted at Larkana satellite center of National Institute of Cardiovascular Diseases, Karachi. Patients who underwent PPCI for STEMI from October 2017 to March 2018 were enrolled in the study. In case of death of the patient, data were obtained from the attendant of the deceased. Patients, on follow-up visits, were interrogated for post-procedure symptoms. Results A total of 271 patients were enrolled in the study. The mean age ± standard deviation of patients was 54.84 ± 10.64 years. The most common culprit artery was left anterior descending (LAD) artery with 161 (59.4%) patients, followed by right coronary artery (RCA) with 98 (36.2%) patients. Only 41 (15%) patients had a three-vessel disease, while 141 (52%) patients had single-vessel disease. On follow-up, 70 (25.8%) patients complained of chest pain grade II, 20 (7.4%) complained of shortness of breath (SOB) grade II, 44 (16.2%) complained of vertigo, and 16 (5.9%) complained of nonspecific weakness. The mortality rate of 6.3% (17) was observed after six months of PPCI. The mortality rate was found to be lower for patients with LAD disease (p = 0.036) and higher among patients with RCA as the culprit artery (p = 0.045). The mortality rate was significantly associated with the number of diseased vessels and the type of stent deployed. Conclusion Primary PCI, at a rural satellite center, has an overall positive outcome. Steps should be taken to provide free medication along with encouragement towards compliance of dual antiplatelet medication. Furthermore, the facility for subsequent procedures should be provided at the same set-up.